Insights on the cGAS-STING Signaling Pathway During Herpesvirus Infections - Deng, Lishuang; Xu, Zhiwen; Li, Fengqin; Zhao, Jun; Jian, Zhijie; Deng, Huidan; Lai, Siyuan; Sun, Xiangang; Geng, Yi; Zhu, Ling (Frontiers in Immunology, 2022)
Herpesviruses belong to large double-stranded DNA viruses. They are under a wide range of hosts and establish lifelong infection, which creates a burden on human health and animal health. Innate immunity is the host's innate defense ability. Activating the innate immune signaling pathway and producing type I interferon is the host's first line of defense against infectious pathogens. Emerging evidence indicates that the cGAS-STING signaling pathway plays an important role in the innate immunity in response to herpesvirus infections. In parallel, because of the constant selective pressure imposed by host immunity, herpesvirus also evolves to target the cGAS-STING signaling pathway to inhibit or escape the innate immune responses. In the current review, we insight on the classical cGAS-STING signaling pathway. We describe the activation of cGAS-STING signaling pathway during herpesvirus infections and strategies of herpesvirus targeting the this pathway to evade host antiviral response. Furthermore, we outline the immunotherapy boosting cGAS-STING signaling pathway.